Case Report: Misdiagnosis of cellular cervical adenomyoma - Wang, Yuting; Tian, Shuyuan; Han, Xiaoyu; Xu, Yingzi (Frontiers in Oncology, 2025)
BackgroundCellular cervical adenomyoma (CCA) is a rare benign tumor composed of proliferative smooth muscle cells and benign endocervical-type glands. Due to its nonspecific clinical and imaging features, CCA can mimic cervical malignancies, posing a diagnostic challenge.Case presentationA 37-year-old woman presented with irregular vaginal bleeding. Pelvic examination revealed an approximately 3 cm friable mass on the posterior cervical lip. Transvaginal ultrasound (TVUS) showed a well-circumscribed, heterogeneous lesion with mild peripheral vascularity, favoring a cervical leiomyoma. In contrast, magnetic resonance imaging (MRI) demonstrated a 5 × 3 cm cervical mass with T2-weighted hyperintensity (T2WI), marked contrast enhancement, and diffusion restriction with a low apparent diffusion coefficient (ADC), raising concern for cervical carcinoma. The patient underwent hysteroscopic excision and diagnostic curettage. Histopathology confirmed a CCA, characterized by densely proliferative smooth muscle bundles with scattered benign endocervical-type glands, without cytologic atypia, mitotic activity, or stromal invasion. Ultrasound at 2 months showed no recurrence; at 12-month telephone follow-up, the patient reported regular menses without abnormal bleeding, although objective long-term surveillance remains necessary.DiscussionThis case highlights the potential for CCA to mimic cervical cancer on MRI due to overlapping features. This case underscores the importance of considering CCA in the differential diagnosis of cervical masses with malignancy-like MRI features and highlights the need for histopathological confirmation to avoid misdiagnosis and overtreatment.